Extracranial Carotid and Vertebral Artery Dissection - Kobza, Ihor I.; Mota, Yuliia S. (Ukrainian Journal of Cardiovascular Surgery, 2024)
Cervical artery dissection (CAD) is a rare vascular pathology that causes stroke in 2.0% of cases and is the most common cause of ischemic stroke among young patients. Today the choice of optimal treatment of CAD remains controversial, especially the issue of choosing antiplatelet and anticoagulant therapy, the expediency of endovascular and surgical approaches. The aim. To analyze the results of management of extracranial carotid and vertebral artery dissection. Materials and methods. Retrospective and prospective analysis of the results of comprehensive examination and treatment in 40 patients (17 [42.5%] men and 23 [57.5%] women, mean age 48.7 ± 13.4 years) with CAD was performed. Of these, 14 (35.0%) patients underwent surgical management, 26 (65.0%) received conservative treatment. Results. Etiology of CAD included: atherosclerosis in 13 (32.5%), fibromuscular dysplasia in 12 (30.0%), trauma in 3 (7.5%), and nonspecific aortoarteritis in 1 (2.5%) patient. Spontaneous CAD was observed in 11 (27.5%) patients. The choice of surgical tactics in patients with carotid artery dissection was justified due to lesion of proximal extracranial segment with unstable ulcerative atherosclerotic plaque, critical stenosis, dissecting aneurysm. The choice of optimal anticoagulant and antiplatelet therapy in conservative group was predicted by individual approach, including the risk of bleeding and ischemic stroke. Long-term results were evaluated among 22 patients who received conservative treatment. Complete resolution of dissection was noted in 15 (68.2%), partial in 4 (18.2%), recurrence of dissection in 1 (4.5%) patient. In 9 (40.9%) patients, complete resolution of dissection was observed within 6 months of treatment. Conclusion. The choice of anticoagulant and antiplatelet therapy of CAD requires an individual approach with evaluation of the risk of bleeding, ischemic stroke, duration of the disease, lumen recanalization, atherosclerotic lesion, patient’s comorbidity. Novel oral anticoagulants and their combination with antiplatelets allow to achieve effective results of treatment of CAD and prevent the recurrence of ischemic events.